Are there reliable and valid measures of anxiety for people with psychosis? A systematic review of psychometric properties. (27th December 2019) - Smith, Emma L.; Garety, Philippa A.; Harding, Helen; Hardy, Amy
Abstract : Purpose: Current models of psychosis posit a developmental and maintaining role for anxiety, supported by robust empirical evidence. Given the central role for anxiety in psychosis, valid and reliable assessment is necessary. This systematic review is the first to critically appraise measures of anxiety applied to psychosis samples. Methods: Web of Science, MEDLINE, PsycINFO, EMBASE, and CINAHL were systematically searched for studies evaluating psychometric properties of instruments measuring anxiety in samples with non‐affective psychosis diagnoses. Psychometric properties were extracted and rated according to established criteria. The COnsensus‐based Standards for the selection of health Measurement Instruments (COSMIN) checklist was used to assess the methodological quality of studies. Results: Of 4, 344 records identified, 11 studies were identified as eligible for inclusion, by two independent raters with high reliability. Reported psychometric properties for 17 different instruments ranged from unacceptable to excellent. The Scale of Anxiety Evaluation in Schizophrenia was assessed most extensively and demonstrated consistently good psychometric properties. The Beck Anxiety Index, Depression Anxiety Stress Scale, DSM‐based Generalised Anxiety Disorder Symptoms Severity Scale, Liebowitz Social Anxiety Scale, Obsessive–Compulsive Inventory, Psychological Stress Index, Perseverative Thinking Questionnaire, and Yale‐Brown Obsessive Compulsive Scale demonstrated adequate reliability and/or validity on the limited properties reported. Methodological quality was largely poor according to the requirements of the COSMIN checklist. Conclusions: The instruments listed are recommended as at least adequate for the assessment of anxiety in psychosis on the basis of these preliminary data. Further validation of existing instruments designed to measure anxiety in people with psychosis is strongly recommended. Practitioner points: Anxiety has a developmental and maintaining role in psychosis; therefore, we should routinely screen for symptoms of anxiety when working with people with psychosis spectrum disorders. Studies included in this review reported reliable and valid measures of anxiety for people with psychosis; however, the methodological quality of most studies was poor. We recommend the BAI, DASS, or SAES for general screening, and the DGSS, LSAS, OCI, PSI, PTQ, and Y‐BOCS to assess symptoms associated with specific anxiety disorders and anxiety‐related processes.